ACADEMIC VARIABLES THAT INFLUENCE THE ACADEMIC PERFOMANCE OF COLLEGE STUDENTS - Ocaña Fernández, Yolvi (2014)
The objective of this article is to describe the variables that influence the academic achievement and its importance in the performance of the students. It describes the process of changes in the higher education during the last century, at global and national level. At the national level, the question is if whether these changes have improved the quality of college education. In the second part, it describes and analyzes the academic variables that influence the academic performance of the students. These variables have been validated in different researches, its knowledge and its study could bring an improving of college education.